MEASUREMENT OF STUDENTS’ SATISFACTION IN LIEPAJA UNIVERSITY - Ilma Neimane (European Scientific Journal, ESJ, 2014)
Higher education establishments are very important in implementation of European Union strategy “Europe 2020”, respectively in advance and maintenance of growth. Main educational target of Europe 2020 strategy is to achieve that 40% of youth would graduate successfully the tertiary education by 2020. The preventive work performed by higher educational establishments is important to achieve the aim that is partially justified with the analysis of students’ inquiry data and conceptualization of obtained conclusion. Liepaja University (hereinafter – LiepU) implements a quality management system (hereinafter – QMS) in accordance with the requirements of the standard ISO 9001:2009. QMS has developed procedures that regulate the measurement of overall student satisfaction. Accreditation provisions of study programmes of the institution of higher education or college and study direction were adopted in 2013 in the Cabinet of Ministers on the base of the Law on Institutions of Higher Education were it is determined that “... the Ministry of Education and Science or the authorized institution elaborates and the Committee for the Accreditation of Studies approves the compulsory issues to be included in the questionnaire of students, employers and graduates”. At this moment such document is not elaborated, however the higher educational establishments, being aware of the development possibilities of their activity, summarize themselves information on the aforementioned issues, and especially on satisfaction of students with the study programs they have chosen. It’s a topical matter to introduce the guidelines elaborated by the European Association for Quality Assurance in Higher Education which anticipate that the educational establishments provide not only gathering and analysis of information required for efficient management of curricula and other activities, but also application thereof. Aim of the research was to detect the criteria for measurements of satisfaction of students offered in current European normative documents and update importance thereof not only the internal quality provisions system of Liepaja University, but also in implementation of the study programs.